Association between Body Mass Index and the Use of Digital Platforms to Record Food Intake: Cross-Sectional Analysis - Héctor José Tricás-Vidal; María Concepción Vidal-Peracho; María Orosia Lucha-López; César Hidalgo-García; Sofía Monti-Ballano; Sergio Márquez-Gonzalvo; José Miguel Tricás-Moreno (Applied Sciences, 2022)
An inadequate diet has been shown to be a cause of obesity. Nowadays, digital resources are replacing traditional methods of recording food consumption. Thus, the objective of this study was to analyze a sample of United States of America (USA) residents to determine if the usage of any meal tracker platform to record food intake was related to an improved body mass index (BMI). An analytical cross-sectional study that included 896 subjects with an Instagram account who enrolled to participate in an anonymous online survey was performed. Any meal tracker platform used to record food intake over the last month was employed by 34.2% of the sample. A total of 85.3% of the participants who had tracked their food intake were women (p < 0.001), and 33.3% (p = 0.018) had a doctorate degree. Participants who used any meal tracker platform also had higher BMIs (median: 24.9 (Q1: 22.7–Q3: 27.9), p < 0.001), invested more hours a week on Instagram looking over nutrition or physical activity (median: 2.0 (Q1: 1.0–Q3: 4.0), p = 0.028) and performed more minutes per week of strong physical activity (median: 240.0 (Q1: 135.0–Q3: 450.0), p = 0.007). Conclusions: USA residents with an Instagram account who had been using any meal tracker platform to record food intake were predominantly highly educated women. They had higher BMIs despite the fact they were engaged in stronger exercise and invested more hours a week on Instagram looking over nutrition or physical activity.